Typology and Grammatical Alignment of Angkola Language - Siregar, Elitaria Bestri; Mulyadi, Mulyadi (Technium Social Sciences Journal, 2020)
This study uses the theory of language typology by Comrie (1988). This research on grammatical alliance of Angkola language (AL) aims to understand (1) the basic construction of clause, (2) the construction of complex sentence, (3) the pivot system, and (4) the grammatical alliance system. The method used is participant-observation. Pivot test revelas that Angkola language syntactically treats S equals to A, and gives different treatment to P (S` = `A` ? P). Angkola language grammatically has an S/A pivot. It can be concluded that AL has a tendency as an accusative language.